EXOTICISM IN FURNITURE DESIGN (Innovation in Woodworking Industry and Engineering design, 2026)
This paper deals with research on different manifestations of exoticism as a strategy for innovation in design and form-building of furniture. The interest in exotic and distant cultures and their art gives rise to a tendency: the emergence of culture mix. Decorative design elements from the East are being integrated with existing furniture types in Europe, or are used to create new ones. The study is done by selecting examples and commenting the phenomena of exoticism in interior and furniture, observed in the works of architects and cabinet-makers from the past. The art of Asia influenced both royal persons and common people long before the development of modern transportation and media widened the horizon.